Tranilast protects from sepsis-induced acute kidney injury in rat via the STAT-3 signaling pathway - Erdoğan, Mümin Alper; Erdoğan, Arife; Erbaş, Oytun (The European Research Journal, 2025)
Objectives: Sepsis-induced acute kidney injury (SI-AKI) is a major contributor to morbidity and mortality among critically ill patients. This experimental study evaluated the renoprotective effects of Tranilast, an anti-inflammatory and antifibrotic agent, in a rat model of polymicrobial sepsis, with a focus on modulation of the signal transducer and activator of transcription 3 (STAT-3) signaling pathway. Methods: Thirty-six female Wistar albino rats were randomly assigned to three groups: Sham control, cecal ligation and puncture (CLP)+saline, and CLP+Tranilast (300 mg/kg/day). Sepsis was induced by CLP. Survival was monitored for five days. Biochemical parameters including plasma tumor necrosis factor alpha (TNF-α), neutrophil gelatinase-associated lipocalin (NGAL), heat shock protein 27 (HSP-27), malondialdehyde (MDA), blood urea nitrogen (BUN), and renal STAT-3 expression were assessed via ELISA and spectrophotometric assays. Histopathological evaluation of renal tissues was performed to assess tubular injury, inflammation, and hemorrhage. Results are expressed as mean±standard error of the mean (SEM). Results: Tranilast significantly improved survival in septic rats (75% vs. 50% in CLP+saline), reduced plasma MDA and TNF-α levels, lowered BUN and NGAL concentrations, and suppressed renal STAT-3 expression (P<0.05). It also enhanced HSP-27 levels, suggesting activation of cytoprotective responses. Histological analysis demonstrated reduced tubular necrosis, luminal debris, inflammation, and hemorrhage in Tranilast-treated rats. Conclusions: Tranilast provides significant renoprotection in SI-AKI by reducing oxidative stress, inflammation, and STAT-3 activity while enhancing cytoprotective mechanisms. These findings support its potential as an adjunctive therapeutic agent for managing sepsis-related organ injury.